Interventions to address global inequity in diabetes: international progress - Ashby F Walker; Sian Graham; Louise Maple-Brown; Leonard E Egede; Jennifer A Campbell; Rebekah J Walker; Alisha N Wade; Jean Claude Mbanya; Judith A Long; Chittaranjan Yajnik; Nihal Thomas; Osagie Ebekozien; et al. (My University, 2023)
Diabetes is a serious chronic disease with high associated burden and disproportionate costs to communities based on socioeconomic, gender, racial, and ethnic status. Addressing the complex challenges of global inequity in diabetes will require intentional efforts to focus on broader social contexts and systems that supersede individual-level interventions. We codify and highlight best practice approaches to achieve equity in diabetes care and outcomes on a global scale. We outline action plans to target diabetes equity on the basis of the recommendations established by The Lancet Commission on Diabetes, organising interventions by their effect on changing the ecosystem, building capacity, or improving the clinical practice environment. We present international examples of how to address diabetes inequity in the real world to show that approaches addressing the individual within a larger social context, in addition to addressing structural inequity, hold the greatest promise for creating sustainable and equitable change that curbs the global diabetes crisis.